What Happens to Diet and Child Health When Migration Splits Households? Evidence from a Migration Lottery Program - Gibson, John; McKenzie, David; Stillman, Steven (2012)
The impact of migration on food security and child health is likely to differ depending on whether children themselves migrate or whether they remain behind while other household members migrate. However, existing studies have not been able to examine how impacts differ in these two scenarios because parallel data are required for both the sending and receiving country. Moreover, self-selection into migration makes unbiased estimation of either impact difficult. We overcome these problems by using a unique survey of Tongan households that applied to migrate to New Zealand through a migrant quota which selects households through a random ballot. This survey covers both migrant children in New Zealand and non-migrant children in Tonga, with the migration policy rules providing a source of exogenous variation for identifying impacts. Our estimates of short-run impacts show that diets diverge upon migration: children who migrate experience improvements, while diets worsen for children who remain. There is also suggestive evidence of a divergence in health outcomes, with increases in weight-for-age and height-for-age found for migrant children, and decreases found for children who remain behind while other household members migrate.